Experimental evidence for limited in vivo virulence of Mycobacterium africanum - Cá, Baltazar (2021)
Funding Information: The authors thank the excellent support from the i3S scientific platforms, namely Animal Facility and Translational Cytometry. Funding. This work was supported by Fundo Europeu de Desenvolvimento Regional funds through the COMPETE 2020 ? Operational Programme for Competitiveness and Internationalization (POCI), Portugal 2020, and by Portuguese funds through Funda??o para a Ci?ncia e a Tecnologia, Minist?rio da Ci?ncia, Tecnologia e Inova??o in the framework of the project ?Institute for Research and Innovation in Health Sciences? (POCI-01-0145-FEDER-007274), and by grants FCT ? Aga Khan Development Network (ref 333197025), POCI-01-0145-FEDER-028955 (to MS), PTDC/BIA-MIC/30692/2017, and UID/Multi/04413/2013 (to DM and MV). BC and KF were funded by FCT Ph.D. scholarships SFRH/BD/114403/2016 and SFRH/BD/114405/2016, respectively. The Gulbenkian Foundation is acknowledged for a field work research grant to BC, Bolsas de apoio ? investiga??o para estudantes de doutoramento dos PALOP, Ref. P-146397. DM and MS were supported by FCT through Estimulo Individual ao Emprego Cient?fico. Publisher Copyright: © Copyright © 2019 Cá, Fonseca, Sousa, Maceiras, Machado, Sanca, Rabna, Rodrigues, Viveiros and Saraiva.